Adalimumab added to a treat-to-target strategy with methotrexate and intra-articular triamcinolone in early rheumatoid arthritis increased remission rates, function and quality of life. The OPERA Study: an investigator-initiated, randomised, double-blind, parallel-group, placebo-controlled trial. Issue 4 (23rd February 2013) - Hørslev-Petersen, Kim; Hetland, Merete Lund; Junker, Peter; Pødenphant, Jan; Ellingsen, Torkell; Ahlquist, Palle; Lindegaard, Hanne; Linauskas, Asta; Schlemmer, Annette; Dam, Mette Yde; Hansen, Ib; Horn, Hans Christian; et al.
Abstract : Objectives: An investigator-initiated, double-blinded, placebo-controlled, treat-to-target protocol (Clinical Trials:NCT00660647 ) studied whether adalimumab added to methotrexate and intra-articular triamcinolone as first-line treatment in early rheumatoid arthritis (ERA) increased the frequency of low disease activity (DAS28CRP<3.2) at 12 months. Methods: In 14 Danish hospital-based clinics, 180 disease-modifying anti-rheumatic drugs (DMARD)-naïve ERA patients (<6 months duration) received methotrexate 7.5 mg/week (increased to 20 mg/week within 2 months) plus adalimumab 40 mg every other week (adalimumab-group, n=89) or methotrexate+placebo-adalimumab (placebo-group, n=91). At all visits, triamcinolone was injected into swollen joints (max. four joints/visit). If low disease activity was not achieved, sulfasalazine 2 g/day and hydroxychloroquine 200 mg/day were added after 3 months, and open-label biologics after 6–9 months. Efficacy was assessed primarily on the proportion of patients who reached treatment target (DAS28CRP<3.2). Secondary endpoints included DAS28CRP, remission, Health Assessment Questionnaire (HAQ), EQ-5D and SF-12. Analysis was by intention-to-treat with last observation carried forward. Results: Baseline characteristics were similar between groups. In the adalimumab group/placebo group the 12-month cumulative triamcinolone doses were 5.4/7.0 ml (p=0.08). Triple therapy was applied in 18/27 patients (p=0.17). At 12 months, DAS28CRP<3.2 was reached in 80%/76% (p=0.65) and DAS28CRP was 2.0 (1.7–5.2) (medians (5th/95th percentile ranges)), versus 2.6 (1.7–4.7) (p=0.009). Remission rates were: DAS28CRP<2.6: 74%/49%, Clinical Disease Activity Index≤2.8: 61%/41%, Simplified Disease Activity Index<3.3: 57%/37%, European League Against Rheumatism/American College of Rheumatology Boolean: 48%/30% (0.0008<p<0.014, number-needed-to-treat: 4.0–5.4). Twelve months HAQ, SF12PCS and EQ-5D improvements were most pronounced in the adalimumab group. Treatments were well tolerated. Conclusions: Adalimumab added to methotrexate and intra-articular triamcinolone as first-line treatment did not increase the proportion of patients who reached the DAS28CRP<3.2 treatment target, but improved DAS28CRP, remission rates, function and quality of life in DMARD-naïve ERA.